Kata Netizen tentang Kesetaraan Gender dalam Sentimen Warganet Twitter - Azkiya, Azka Al; Vega, Iliana Patricia; Iqbal, M.; Fatimah, Zahra Nurul; Syafitri, Utami Dyah (UIN Sayyid Ali Rahmatullah Tulungagung, Indonesia, 2021)
Abstract: Gender equality is one of the goals in the Sustainable Development Goals. However, until now Indonesia is still having difficulties in achieving this goal. According to the United Nations Development Program (UNDP) data, Indonesia's Gender Inequality Index (GII) is ranked 107 out of 189 countries. In addition, according to The Global Gender Gap Index 2021 data by the World Economic Forum (WEF), Indonesia is ranked 105th out of 153 countries. This shows that Indonesia is still lagging behind in terms of gender equality. Therefore, this study aims to analyze the sentiments of Indonesian twitter netizens regarding gender equality in 2018-2021 and its accuracy. Data was collected from primary data, scraping twitter data with the keywords #kesetaraan and #gender in Indonesian. The method used is Lexicon-based Sentiment Analysis with AFINN-111 dictionary translated into Indonesian. The results obtained are that the percentage of positive sentiments tends to decrease from year to year except for 2021. On the contrary, the negative sentiments of Twitter tend to increase. This is due to controversial articles in RKUHP, RUU Cipta Kerja, Covid-19 pandemic, and the online gender-based violence. This shows that the gender equality in Indonesia is still minimal and needs to be improved. Keywords: AFINN-111, gender equality, lexicon-based sentiment analysis, text mining, twitter Abstrak: Kesetaraan gender termasuk tujuan pada Sustainable Development Goals. Namun hingga saat ini Indonesia masih kesulitan dalam mencapai tujuan tersebut. Menurut data United Nations Development Programme (UNDP), nilai Gender Inequality Index (GII) Indonesia menempati peringkat 107 dari 189 negara. Selain itu, menurut data The Global Gender Gap Index 2021 dari World Economic Forum (WEF), Indonesia menempati posisi ke-105 dari total 153 negara. Hal ini membuktikan gender di Indonesia masih belum setara. Oleh karena itu, penelitian ini bertujuan untuk menganalisis sentiment netizen twitter Indonesia mengenai kesetaraan gender pada 2018-202i dan akurasinya. Data dikumpulkan dari data primer yaitu scraping data twitter dengan keyword #kesetaraangender dan #gender dalam Bahasa Indonesia. Metode yang digunakan adalah Lexicon-based Sentiment Analysis dengan bantuan kamus AFINN-111 yang diterjemahkan dalam Bahasa Indonesia pada software python. Hasil yang diperoleh adalah persentase sentimen positif netizen twitter cenderung menurun dari tahun ke tahun kecuali 2021, sebaliknya sentimen negatif netizen twitter cenderung meningkat setiap tahun. Hal ini dikarenakan adanya pasal yang mengandung kontroversi pada Rancangan Kitab Undang-undang Hukum Pidana (RKUHP), RUU Cipta Kerja, adanya pandemi Covid-19, dan maraknya kekerasan berbasis gender online. Hal ini menunjukkan bahwa tingkat kesetaraan gender di Indonesia masih minim dan perlu untuk ditingkatkan kedepannya. Kata kunci: AFINN-111, kesetaraan gender, lexicon-based sentiment analysis, text mining, twitter